2019
DOI: 10.1038/s41598-019-50802-z
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive real-space imaging of energy dissipation distributions in randomly networked conductive nanomaterials

Abstract: For realization the new functional materials and devices by conductive nanomaterials, how to control and realize the optimum network structures are import point for fundamental, applied and industrial science. In this manuscript, the nondestructive real-space imaging technique has been studied with the lock-in thermal scope via Joule heating caused by ac bias conditions. By this dynamical method, a few micrometer scale energy dissipations originating from local current density and resistance distributions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It is to be noted, however, that there are different processes contributing to the thermal image; radiation emission produced by direct power dissipation due to Joule heating produces radiation in phase with the current, while diffusive processes have a delay in emission. [53][54][55] As observed in Figure 2d, a localized region of close to zero phase matches with the main trace observed in Figure 2c. This low-phase region is produced as radiation is emitted locally and directly within the current transmission pathways, either by the nanowire junctions, the nanowires, or the contact point between the nanowires and the substrate.…”
Section: (4 Of 11)supporting
confidence: 84%
See 1 more Smart Citation
“…It is to be noted, however, that there are different processes contributing to the thermal image; radiation emission produced by direct power dissipation due to Joule heating produces radiation in phase with the current, while diffusive processes have a delay in emission. [53][54][55] As observed in Figure 2d, a localized region of close to zero phase matches with the main trace observed in Figure 2c. This low-phase region is produced as radiation is emitted locally and directly within the current transmission pathways, either by the nanowire junctions, the nanowires, or the contact point between the nanowires and the substrate.…”
Section: (4 Of 11)supporting
confidence: 84%
“…[47] Typically, LIT has been used for operation and failure analyses of electronic devices, including solar cells. [47,48] In recent years, the technique has also been used to unveil new fundamental physical phenomena, with important results in spin caloritronics, [49][50][51][52] as well as to directly visualize power dissipation and heat transmission in different nanomaterials, including carbon nanotube composites, [53] highly conductive nanowire networks, [54] or defects in large sheets of graphene. [55] This technique offers direct insight into the importance of defects and geometry in the fabrication of these materials.…”
Section: (4 Of 11)mentioning
confidence: 99%
“…To do so two non-invasive techniques are studied that can measure in one go the distributed conductive properties and which potentially can be used to study both DC and AC characteristics. Here we show that IR thermography, so far used for studying heating power in 3D-printed samples [5], can also be used for studying the anisotropic electrical properties of 3D-printed samples as it has been done for the characterization of carbon fiber reinforced polymers [9], conductive textiles [10], micro-irregularities in electronic components [11], [12] and to image networked conductive nanomaterials [13]. In this paper we also show that the voltage contrast scanning electron microscopy method (VCSEM), used e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that LIT can effectively characterize the CNT network in centimeter-scale CNT/rubber and resin composites. 16,17 LIT is an excellent evaluation technique for observing the dispersion and conductive behavior of CNT llers in CNT composites. Its unique ability to visualize conductive networks at the nanoscale, simultaneously measure electrical properties, and provide both numerical and mapping information makes it a powerful tool for studying the dispersion state of CNTs in 3D, including during material deformation.…”
Section: Introductionmentioning
confidence: 99%